2013
DOI: 10.1248/cpb.c13-00456
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Exploitation of AZADO: The Highly Active Catalyst for Alcohol Oxidation

Abstract: The oxidation of primary and secondary alcohols to the corresponding aldehydes (or carboxylic acids) or ketones is a fundamental transformation in organic synthesis. Stable organic nitroxyl radicals as represented by 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) (1) have been used extensively to catalyze the oxidation of a number of alcohol substrates employing environmentally benign co-oxidants such as bleach (NaOCl) or PhI(OAc) 2 . Although TEMPO oxidation is better known as a method for selective oxidation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(52 citation statements)
references
References 47 publications
(68 reference statements)
1
51
0
Order By: Relevance
“…In addition, electrochemical detection of lidocaine, a local anesthetic containing a tertiary amine structure, was demonstrated using NNO with a calibration curve of 0.1-10 mM.around the nitroxyl radical active site, and an adequate response current could not be obtained under physiological conditions. Iwabuchi and colleagues [22] reported that 2-azaadamantane N-oxyl (AZADO), which lacks steric hindrance around the active site, exhibited greater activity than TEMPO in organic synthesis reactions. Less-hindered nitroxyl radicals with various steric environments have been synthesized, and those with less bulky functionality exhibited greater activity [23][24][25][26].…”
mentioning
confidence: 99%
“…In addition, electrochemical detection of lidocaine, a local anesthetic containing a tertiary amine structure, was demonstrated using NNO with a calibration curve of 0.1-10 mM.around the nitroxyl radical active site, and an adequate response current could not be obtained under physiological conditions. Iwabuchi and colleagues [22] reported that 2-azaadamantane N-oxyl (AZADO), which lacks steric hindrance around the active site, exhibited greater activity than TEMPO in organic synthesis reactions. Less-hindered nitroxyl radicals with various steric environments have been synthesized, and those with less bulky functionality exhibited greater activity [23][24][25][26].…”
mentioning
confidence: 99%
“…In the last decades, due to the great success of TEMPO mediated oxidations, many similar reagents have been developed, and in several cases the latter have proved to be more efficient than TEMPO progenitor . However, since their reactivity applied to the oxidative transposition of tertiary allylic alcohols is practically unknown, especially in water, we decided to test some of them, i. e. keto‐ABNO, ABNO and its oxoammonium tetrafluoroborate salt together with the progenitor TEMPO (Figure , for the preparation of oxoammonium salts see SI);, the results of this screening are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The lack of reactivity of secondary alcohols was attributed to steric hindrance in the abstraction of an α-hydrogen atom from a coordinated alkoxide by a coordinated TEMPO ligand. Consequently, the use of sterically less hindered nitroxyl radicals such as AZADO and ABNO, respectively, in combination with Cu(I) complexes, were developed by the groups of Iwabuchi (Shibuya et al, 2006(Shibuya et al, , 2011Iwabuchi, 2013) and Stahl (Steves and Stahl, 2013), for the aerobic oxidation of secondary alcohols (Figure 3), including sterically demanding alcohols such as menthol and a variety of unprotected amino alcohols (Sasano et al, 2014).…”
Section: Catalytic Oxidationsmentioning
confidence: 99%